Happy Birthday (Kioon Records/Sony Music Japan, 2011)
Single and album track with the Japanese artist duo PUFFY.This year, pop duo PUFFY will be celebrating their 15th anniversary with the release of a new single: “Happy Birthday” on February 9th, along with a new album: “Thank You!,” on March 9th. The melody is written by David Myhr together with succesful Swedish songwriter/producer Peter Kvint.The duo originally debuted with the Okuda Tamio producing the joint single: “Asia no Jyunshin” on May 13th 1996. Their new single album “Happy Birthday” will be in celebration of their 15th anniversary and will feature the title tracks: Eskimo “MOW” CM song “Banzai!,” as well as “Gingakei Drive“; recorded during their 2009 tour. “Happy Birthday” will be released in regular CD and limited edition first print versions, and the limited edition copy will come with a DVD that contains footage from their 2010 summer tour at the Hitomi Memorial Hall.The new album “Thank You!” will express the gratitude for their success that the two members feel. It will also be released in CD regular and limited first print editions. The limited edition will retail at 3939 yen and more details on its bonus features will be released at a later date.On top of all the new releases coming out from PUFFY this spring they will also be going on tour from April through May. The “PUFFY 15th Anniversary Tour ‘Thank You!‘” kicks off at the Osaka Nanba Hatch on April 2nd and runs until May 14th at the Tokyo Hibiya Outdoor Music Hall. Singel och albumspår med den japanska artistduon PUFFY.This year, pop duo PUFFY will be celebrating their 15th anniversary with the release of a new single: “Happy Birthday” on February 9th, along with a new album: “Thank You!,” on March 9th. The melody is written by David Myhr together with succesful Swedish songwriter/producer Peter Kvint.The duo originally debuted with the Okuda Tamio producing the joint single: “Asia no Jyunshin” on May 13th 1996. Their new single album “Happy Birthday” will be in celebration of their 15th anniversary and will feature the title tracks: ...